First observation of the decay λ0b→ηc(1S)pK- - Aaij, Roel; Archilli, Flavio; Bachmann, Sebastian; Berninghoff, Daniel; Borsato, Martino; Dziewiecki, Michal; Frau, Giulia; Gerick, David; Grabowski, Jascha; Günther, Paul André; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; et al. (Physical review, 2020)
The decay Λ0b→ηc(1S)pK− is observed for the first time using a data sample of proton-proton collisions, corresponding to an integrated luminosity of 5.5 fb−1, collected with the LHCb experiment at a center-of-mass energy of 13 TeV. The branching fraction of the decay is measured, using the Λ0b→J/ψpK− decay as a normalization mode, to be B(Λ0b→ηc(1S)pK−)=(1.06±0.16±0.06+0.22−0.19)×10−4, where the quoted uncertainties are statistical, systematic and due to external inputs, respectively. A study of the ηc(1S)p mass spectrum is performed to search for the Pc(4312)+ pentaquark state. No evidence is observed and an upper limit of B(Λ0b→Pc(4312)+K−)×B(Pc(4312)+→ηc(1S)p)B(Λ0b→ηc(1S)pK−)<0.24 is obtained at the 95% confidence level.